Study on physical, morphological and strength properties of jana manjung ash mixture - Asyraf Nasuha Mohd Yunus (School of Environmental Engineering, University Malaysia Perlis, 2013)
This study focuses on some properties of fly ash, bottom ash and mixture of them from Manjung power plant.